More trust in networks, more secure keys - Guan-Jie Fan-Yuan; Shuang Wang (Light: Science & Applications)
Abstract A novel continuous-variable quantum passive optical network is proposed in which a user can increase their key rate by trusting other users. This is because the keys, which would be discarded to remove correlations with untrusted users, can be retained when the users are trusted. It provides a new perspective for enhancing network performance.